1999
DOI: 10.1152/ajpgi.1999.276.6.g1313
|View full text |Cite
|
Sign up to set email alerts
|

V. Therapeutic potential of nitric oxide donors and inhibitors

Abstract: Nitric oxide is a crucial mediator of gastrointestinal mucosal defense, but, paradoxically, it also contributes to mucosal injury in several situations. Inhibitors of nitric oxide synthesis and compounds that release nitric oxide have been useful pharmacological tools for evaluating the role of nitric oxide in gastrointestinal physiology and pathophysiology. Newer inhibitors with selectivity for one of the isoforms of nitric oxide synthase are even more powerful tools and may have utility as therapeutic agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
1
5

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 21 publications
0
91
1
5
Order By: Relevance
“…L-NAME and D-NAME were injected intraperitoneally (i. p.), at a dose of 50 mg/kg, 24 h and 30 min before venom injection [20]. Aminoguanidine, an inhibitor of iNOS [22], was administered i. p. 24 h and 30 min before venom injection, at doses of 50 mg/kg and 100 mg/kg, respectively [20]. Sodium nitroprusside was used in experiments dealing with edema and myonecrosis, and was injected subcutaneously (s.c.) (for edema) and intramuscularly (i. m.) (for myonecrosis), at a dose of 5 mg/kg.…”
Section: Protocols Used For Administration Of Drugsmentioning
confidence: 99%
“…L-NAME and D-NAME were injected intraperitoneally (i. p.), at a dose of 50 mg/kg, 24 h and 30 min before venom injection [20]. Aminoguanidine, an inhibitor of iNOS [22], was administered i. p. 24 h and 30 min before venom injection, at doses of 50 mg/kg and 100 mg/kg, respectively [20]. Sodium nitroprusside was used in experiments dealing with edema and myonecrosis, and was injected subcutaneously (s.c.) (for edema) and intramuscularly (i. m.) (for myonecrosis), at a dose of 5 mg/kg.…”
Section: Protocols Used For Administration Of Drugsmentioning
confidence: 99%
“…Previous researches were in agreement with our results showing that γ-irradiation may enhance endogenous NO biosynthesis in liver, intestine, lung, kidney, brain, spleen or heart of the animals, presumably by facilitating the entry of Ca2+ ions into the membrane as well as the cytosol of NO-producing cells through irradiation induced membrane lesions (Hong et al, 2013). Conversely, it has been demonstrated that NO donors can ameliorate the intestinal injuries in experimental colitis on the basis that NO might inhibit neutrophil infiltration (an important step in the development of I/R injury) and improve microcirculation resulting from its vasodilatory effect (Muscará and Wallace, 1999). .…”
Section: Discussionmentioning
confidence: 99%
“…All these chemical constituents are also present in Neoglaziovia variegata, which probably explains the similarity between the results of these studies. According to Muscara and Wallace (1999), NO is partially involved in mucus and bicarbonate secretion. Sugita et al (2003) reported cytoprotective effects for this compound on ethanol-induced gastric lesions.…”
Section: Discussionmentioning
confidence: 99%